Implementation of Participatory Design Method in the Design Process of the Female Students' Dormitory at SMPIT Tahfidzul Qur'an Ibnul Mubarak - Puteri Fitriaty; Rifai Mardin; Iwan Setiawan Basri; Andi Jiba Rifai Bassaleng; Nur Rahmanina Burhany; Burhanuddin (Universitas Muhammadiyah Surakarta, 2025)
As private educational institution, The “Ibnul Mubarak” Educational Foundation requires adequate facilities and infrastructure, including a dormitory building. However, with limited capital, this foundation needs a flexible and efficient design. The available site is located in Palu, and constrained by limited space approximately 589 m² and should accommodate approximately 75-80 users. This presents some challenges in providing a design concept that complies to the needs of all building users. This community service aim at addressing the challenges faced by the “Ibnul Mubarak” Educational Foundation by developing a design for female student dormitory that is urgently needed including classroom, office, laboratories, kitchen, lavatory, bathroom, ablution room, coop room, and school keeper's house. The design should adhere to the standards of integrated Islamic secondary education. To achieve this, the project employs various methods, including participatory design, mentoring, and interactive design. The design process and working drawings are developed using Building Information Modelling (BIM) software, specifically Revit 2024. This community service positively impacted the foundation by enhancing its teachers’ capacity to overcome design challenges while stimulating creativity to produce a comfortable design. The primary contribution of this community engagement is a proposed design of the “Ibnul Mubarak” Integrated Islamic Secondary School student dormitory along with its supporting facilities. Additionally, recommendations for site and building development planning are also generated as part of this initiative.